2013
DOI: 10.4084/mjhid.2013.010
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Pregnancy

Abstract: Pregnant women have a higher risk of malaria compared to non-pregnant women. This review provides an update on knowledge acquired since 2000 on P. falciparum and P.vivax infections in pregnancy. Maternal risk factors for malaria in pregnancy (MiP) include low maternal age, low parity, and low gestational age. The main effects of MIP include maternal anaemia, low birth weight (LBW), preterm delivery and increased infant and maternal mortality.P. falciparum infected erythrocytes sequester in the placenta by expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
112
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 148 publications
3
112
1
4
Order By: Relevance
“…In sub-Saharan Africa, 25 million pregnant women are currently at risk for malaria, accounting for 10,000 maternal and 200,000 neonatal deaths per year (Matangila et al, 2014;Mbah et al, 2015). In such regions of high transmission and endemicity, sub-clinical malarial infection is common (Takem and D'Alessandro, 2013) and individuals living in such regions usually develop protective immunity to malaria by adolescence; however, this protection is partially abrogated in women during pregnancy, resulting in pregnancy-associated malaria (PAM) (Jaworowski et al, 2009;Takem and D'Alessandro, 2013). Pregnancy-associated malaria results in tremendous obstetrical and paediatric morbidity, including maternal anaemia, intrauterine growth retardation, low birth weight, prematurity, miscarriage, and stillbirth (Tonga et al, 2013;Mbah et al, 2015;White, 2015; Chedraui, Daily and Wylie, 2016; Prahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, 25 million pregnant women are currently at risk for malaria, accounting for 10,000 maternal and 200,000 neonatal deaths per year (Matangila et al, 2014;Mbah et al, 2015). In such regions of high transmission and endemicity, sub-clinical malarial infection is common (Takem and D'Alessandro, 2013) and individuals living in such regions usually develop protective immunity to malaria by adolescence; however, this protection is partially abrogated in women during pregnancy, resulting in pregnancy-associated malaria (PAM) (Jaworowski et al, 2009;Takem and D'Alessandro, 2013). Pregnancy-associated malaria results in tremendous obstetrical and paediatric morbidity, including maternal anaemia, intrauterine growth retardation, low birth weight, prematurity, miscarriage, and stillbirth (Tonga et al, 2013;Mbah et al, 2015;White, 2015; Chedraui, Daily and Wylie, 2016; Prahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The area under the parasitemia curve (AUC) was used as a proxy for blood parasite mass during the infection period in order to compare parasite expansion in P. berghei-and P. berghei-VAR-infected mice. Susceptibility to infection, as determined by parasite expansion in peripheral blood, was increased in pregnant (P) mice compared to nonpregnant (NP) females, irrespective of the infection dose and parasite line (P P. berghei versus NP P. berghei at 10 6 IEs, P Ͻ 0.01; P P. berghei-VAR versus NP P. berghei-VAR at all doses, P Ͻ 0.001; P P. berghei versus NP P. berghei at 10 5 and 10 4 IEs, P Ͻ 0.001) (Fig. 4A to C).…”
Section: Generation and Characterization Of Transgenic P Berghei-varmentioning
confidence: 99%
“…In areas of unstable malaria transmission, pregnant women can develop severe malaria due to low immunity to the parasite, which has been associated with increased mortality during pregnancy (4,5), miscarriages, preterm deliveries, low birth weight, stillbirth, and death of neonates (6). These features can be recapitulated in a mouse model of severe placental malaria (PM) (7), which consists of infection of BALB/c mice syngeneically pregnant with parasites of the ANKA strain of the rodent malaria parasite Plasmodium berghei.…”
mentioning
confidence: 99%
“…This infection affects about 350 to 500 million people with 1 to 3 million deaths, every year (1,2). Malaria infection during pregnancy is a major public health concern with significant risks for the pregnant woman and her fetus (1)(2)(3). Annually, about 125 million women (25 million pregnant women) are at risk of malaria around the world.…”
mentioning
confidence: 99%
“…Over 90% of the world's malaria-related deaths in the world occur in sub-Saharan Africa. It has been reported that in this region malaria can cause as many as 10,000 cases of malaria-related deaths in pregnancy per year, usually due to severe maternal anemia (1)(2)(3)(4)(5). Pregnant women have a reduced immune response to malaria infection.…”
mentioning
confidence: 99%